Meta-analysis of effects of yoga exercise intervention on sleep quality in breast cancer patients - Zhu, Jingzhi; Chen, Xiaojuan; Zhen, Xinxian; Zheng, Huan; Chen, Hong; Chen, Huimin; Liao, Huizhao; Zhu, Jinru; Wang, Chaoyu; Zheng, Zhenzhen; Chen, Riken; Wang, Yang (Frontiers in Oncology, 2023)
Objective: This study seeks to systematically evaluate and test the effects of yoga exercise intervention programs on sleep quality in breast cancer patients in order to suggest more optimized exercise programs. Method: Computer searches of the PubMed, Embase, Cochrane Library, Web of Science and CINAHL databases are conducted to collect randomized controlled trials. Two investigators independently carry out the inclusion and exclusion criteria literature screening, data extraction and methodological quality assessment of the included literature by applying the Cochrane risk of bias tool. Subgroup analysis is performed using RevMan 5.4.1 software, and the six moderating variables of intervention format, intervention type, weekly intervention frequency, total intervention duration, single intervention duration and intervention evaluation at different time points are set for the 782 subjects of the 12 included publications. Results: Twelve randomized controlled trials with a total sample size of 782 subjects are included, including 393 subjects in the experimental group and 389 subjects in the control group. The meta-analysis shows that yoga exercise intervention is effective in improving sleep quality in breast cancer patients [SMD = -0.40, 95% CI: (-0.71, -0.09), P = 0.01]; yoga exercise intervention focusing on positive meditation [SMD = -0.55, 95% CI: (-1.08, -0.03), P = 0.04] is effective in improving sleep; yoga exercise intervention two or three times a week is effective in improving sleep quality [SMD = -0.69, 95% CI: (-1.19, -0.19), P = 0.007]; yoga exercise intervention for 6–8 weeks significantly improves sleep quality [SMD = -0.86, 95% CI: (-1.65, -0.08), P =0.03]; and evaluation immediately after the end of intervention improves sleep outcomes [SMD = -0.17, 95% CI: (-0.33, 0.00), P = 0.05], while differences in sleep quality improvement are not statistically significant for the remaining subgroup outcomes (P > 0.05). Conclusion: The available evidence suggests that yoga exercise intervention has good effects on improving sleep quality in breast cancer patients. Positive meditation intervention type, intervention frequency of two or three times per week, total intervention duration of 6–8 weeks and evaluation immediately after the end of intervention are shown to be effective in improving sleep quality.